2005
DOI: 10.4049/jimmunol.175.12.8024
|View full text |Cite
|
Sign up to set email alerts
|

Fas Ligand Induces Cell-Autonomous IL-23 Production in Dendritic Cells, a Mechanism for Fas Ligand-Induced IL-17 Production

Abstract: Fas ligand (FasL) has the potential to induce inflammation accompanied by massive neutrophil infiltration. We previously reported that FasL rapidly induces the production of various inflammatory cytokines including IL-1β and IL-17. In this study, we investigated the mechanism of the FasL-induced IL-17 production. We found that the culture supernatant of mouse resident peritoneal exudate cells (PEC) cocultured with FasL-expressing tumor (FFL) cells induced IL-17 production in freshly isolated resident PEC. Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…2B). We also found that IL-23 but not IL-12 induced IL-17 production in resident peritoneal exudate cells (44). To further confirm the importance of IL-23 in the induction of IL-17 after M. bovis BCG i.t.…”
Section: Expression Of Il-17 and Il-17-inducing Cytokine Il-23 In Thementioning
confidence: 55%
“…2B). We also found that IL-23 but not IL-12 induced IL-17 production in resident peritoneal exudate cells (44). To further confirm the importance of IL-23 in the induction of IL-17 after M. bovis BCG i.t.…”
Section: Expression Of Il-17 and Il-17-inducing Cytokine Il-23 In Thementioning
confidence: 55%
“…Altogether, these data support the concept that the development of IL-17 in T cells in mice can be initiated by the TGF-b-IL-6 pathway, but that the induction of fully functional Th17 cells that are protective against bacterial infection or progressors of chronic inflammatory disease depends on IL-23. In addition to IL-23, protection against bacteria requires IL-1 (Zwijnenburg et al, 2003;Miller et al, 2006), which may be explained by the finding that IL-1b and IL-1a synergize with IL-23 in the induction of protective IL-17 by murine Th cells (Kidoya et al, 2005;Sutton et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…However, in humans, this finding has not been confirmed thus far. In addition, both in mice and man, Th17 cells can be induced in memory Th cells by IL-23 (Harrington et al, 2005;Park et al, 2005;Langrish et al, 2005;Aggarwal et al, 2003) and IL-1 (Kidoya et al, 2005;Sutton et al, 2006). The importance of this IL-23-IL-17 axis in antimicrobial immunity is underlined by previous studies showing that protection against Klebsiella pneumoniae (Happel et al, 2005) and Streptococcus pneumoniae (Malley et al, 2006), for example, is impaired in mice deficient in the IL-23-specific subunit p19 or in IL-17.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, Miwa et al (3) and our group have shown that innate inflammatory cytokines such as IL-18 and IL-1b are produced from neutrophils and macrophages via Fas signaling without the induction of apoptosis (4). Furthermore, it has been shown that the production of other cytokines or chemokines is also induced by Fas stimulation (5)(6)(7)(8)(9)(10). These data indicate the possibility that Fas signaling plays important roles in the innate immune system in response to infection by pathogenic microbes; however, the precise molecular mechanisms and physiological roles of inflammatory cytokine production via Fas signaling in bacterial infection are not clear.…”
mentioning
confidence: 99%